GIANT PHYLLODES TUMORS (BENIGN AND MALIGN VARIANT): CLINICAL CHANGES, SURGICAL TREATMENT AND AMBULATORY FOLLOW-UP – CASE REPORTS - Belluco, Rosana Zabulon Feijó (2023)
Phyloid Tumors are rare fibroepithelial tumors of the breast, representing less than 1% of all breast neoplasms, affecting women in the age group with the highest incidence between 40 and 50 years. With a variable biological behavior, the spectrum of benign presentation is confused with cellular fibroadenoma and, not the other extreme, the malignant presents similarities with other malignant neoplasms of the breast. Indicate, appear as a palpable, smooth, multinodular, firm, mobile and painless tumor, with abnormal mammographic and ultrasound findings. Tumor growth is usually rapid, with no correlation with increased risk of malignancy. The diagnosis is confirmed by histopathological evaluation. The treatment is eminently surgical, with excision with free margins and even mastectomy, a tumor-dependent extension being indicated. The presence of margins is important, since this contributes to the reduction of local recurrences, very common in this type of tumor. Adjuvant radiotherapy is controversial in the literature, but it appears to reduce recurrence without changing mortality. This article requires 02 cases of Phyloid Tumor, a benign and malignant variant, with which we aim to emphasize the importance of differential diagnosis and adequate surgical treatment, especially less postoperative morbidity.